Exploring the Physiotherapeutic Correlation Between HbA1c Levels and Generalized Body Ache in Diabetic Individuals - Jain, Rajshri; Chobisa, Chitrakshi A.; Warsi, Rahat Khan; Warhade, Veenodini; Khan, Jafar; Gupta, Sourabh; shah, Yash; pal, Renuka; Ansari, Adil Raza; Rawal, Hardik (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus often leads to systemic complications, including generalized body ache (GBA). HbA1c is a reliable indicator of long-term glycemic control. This study explores the correlation between HbA1c levels and the intensity of GBA in diabetic individuals, investigating the physiotherapeutic significance of isometric exercise in managing such discomfort. Methodology: An observational study was conducted on diabetic individuals with GBA. Participants’ HbA1c levels (from recent lab reports) and baseline pain intensity (measured using the Visual Analogue Scale) were recorded. Statistical analysis was performed to assess the correlation between glycemic control and pain severity. Results: Most participants showed reduced pain intensity post-intervention, with mild correlation trends observed between initial HbA1c levels and severity of body ache. Conclusion: Isometric exercises can be effective in reducing GBA in diabetic patients. A potential physiotherapeutic correlation between higher HbA1c levels and increased pain intensity was observed, warranting deeper studies